The effect of wellness training on specialized simulators on the psychophysical state of middle-aged peopl - Dvorkina N.I. ,; Golubeva G.N. , (Theory and Practice of Physical Culture, 2025)
The study focuses on investigating the impact of recreational water training using specialized AquaGym simulators on the psychophysical state of middle-aged individuals. Water training, leveraging the unique properties of water, helps strengthen the cardiovascular system, muscles, flexibility, and coordination, making it an effective and safe alternative to traditional land-based exercises. The study involved 32 participants aged 30 to 60 and older, who trained on the simulators for periods ranging from 6 months to over 2 years. The results showed that 46.9% of participants experienced significant improvements in well-being, 37.5% reported muscle strengthening, 25% noted increased flexibility, and 18.8% observed reduced stress levels and improved cardiovascular fitness. Most respondents rated the effectiveness of the simulators as "very effective" (31.3%) or "effective" (46.9%). The primary motivation for continuing the training was health improvement (56.3%). In conclusion, the study affirms the positive impact of water training on the psychophysical state of middle-aged individuals.